2016
DOI: 10.1016/j.jid.2016.06.621
|View full text |Cite
|
Sign up to set email alerts
|

The Senescence-Associated Secretory Phenotype: Critical Effector in Skin Cancer and Aging

Abstract: Cellular senescence, a state of stable cell cycle arrest in response to cellular stress, is an indispensable mechanism to counter tumorigenesis by halting the proliferation of damaged cells. However, through the secretion of an array of diverse cytokines, chemokines, growth factors, and proteases known as the senescence-associated secretory phenotype (SASP), senescent cells can paradoxically promote carcinogenesis. Consistent with this, removal of senescent cells delays the onset of cancer and prolongs lifespa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
95
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 91 publications
(105 reference statements)
4
95
0
Order By: Relevance
“…Emerging evidence has demonstrated that the cross‐talk between monocyte‐macrophage‐osteoclasts and bone marrow stromal cells (BMSCs)‐osteoblasts plays a vital role in the pathology of osteoporosis (Cao et al., 2005; Yu, & Wang, 2016). With organismal aging, molecules of the senescence‐associated secretory phenotype (SASP) are secreted into the bone microenvironment by senescent cells (Ghosh, & Capell, 2016; Lim, Park, Shin, Kwon, & Kim, 2017). These molecules attenuate osteogenic differentiation as well as promote adipogenic differentiation and senescence of BMSCs, which is considered to be the primary cause of osteoporotic bone loss (Riminucci, Remoli, Robey, & Bianco, 2015; Tsai, & Li, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has demonstrated that the cross‐talk between monocyte‐macrophage‐osteoclasts and bone marrow stromal cells (BMSCs)‐osteoblasts plays a vital role in the pathology of osteoporosis (Cao et al., 2005; Yu, & Wang, 2016). With organismal aging, molecules of the senescence‐associated secretory phenotype (SASP) are secreted into the bone microenvironment by senescent cells (Ghosh, & Capell, 2016; Lim, Park, Shin, Kwon, & Kim, 2017). These molecules attenuate osteogenic differentiation as well as promote adipogenic differentiation and senescence of BMSCs, which is considered to be the primary cause of osteoporotic bone loss (Riminucci, Remoli, Robey, & Bianco, 2015; Tsai, & Li, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, we find that skin cancer induced elevation in the gene and protein expression of NFκB, TNF‐α and IL‐1β. It has been reported that skin cancer induced upregulation of NFκB pathway, which creates a permissive tumor microenvironment that helps the development of drug‐resistance . In addition, resistance to MAPK inhibitors takes place in tumors associated with transcriptional upregulation of NFκB‐driven inflammatory genes .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that skin cancer induced upregulation of NFκB pathway, which creates a permissive tumor microenvironment that helps the development of drug-resistance. [36] In addition, resistance to MAPK inhibitors takes place in tumors associated with transcriptional upregulation of NFκB-driven inflammatory genes. [37] On the other hand, treatment of skin cancer with sulforaphane significantly reduced skin cancer-induced elevation in the gene and protein expression of the inflammatory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…When a telomere reaches a critically short length, the cell stops dividing and reaches a state of cellular senescence, often referred to as the 'Hayflick limit' (16). The Hayflick limit has been demonstrated in a variety of adult cell types in vitro, including fibroblasts (10), endothelial cells (17) and lymphocytes (18), whereby cells exhibit progressively shorter telomeres over increasing passages (or "population doublings"), a gradual reduction in their ability to proliferate, a reduced propensity to undergo programmed cell death, and a maladaptive proinflammatory phenotype (19). The reduced replicative capacity of ageing cells is hypothesized to contribute to age-related tissue-level pathology in vivo; as old, damaged cells, can no longer be replaced with new, healthy cells (20).…”
Section: Introductionmentioning
confidence: 99%